A metric for the real-time evaluation of the aircraft boarding progress. (January 2018) - Schultz, Michael
Highlights: Interactions of passengers in the aircraft cabin are evaluated. The evaluation metric is based on a derived cabin-wide interference potential. Simulation environment is used to demonstrate the basic working principle. This research will enable real-time prediction of the aircraft boarding progress. Abstract: Future 4D aircraft trajectories demand the comprehensive consideration of environmental, economic, and operational constraints. A reliable prediction of all aircraft-related processes along the specific trajectories is essential for punctual operations. The uncertainties in the airborne phase only have minor impacts on the punctuality of a flight. The necessary change to an air-to-air perspective, with a specific focus on the ground operations, will provide key elements for complying with the challenging future requirements of a comprehensive 4D aircraft trajectory over the day of operations. A major task of the ground operations is to ensure a reliable and predictable departure time, which is an operational milestone for both the current and the destination airport. These mutual interdependencies between airports result in system-wide, far-reaching effects (reactionary delays). The ground trajectory of an aircraft primarily consists of the handling processes at the stand (deboarding, catering, fueling, cleaning, boarding, unloading, and loading), which are defined as the aircraft turnaround. To provide a reliable prediction of the turnaround, the critical path of processes has to be managed in a sustainable manner. The turnaround processes are mainly controlled by the ground handling, airport or airline staff, except the aircraft boarding, which is driven by the passengers' experience and willingness or ability to follow the proposed procedures. Addressing the fact that boarding is on the critical path of the aircraft 4D trajectory and not controlled by the operators, this paper provides a scientific approach for a real-time evaluation of the boarding progress using the capabilities of a future connected cabin (e.g. sensor environment). A calibrated microscopic approach is used to model the distinct passenger behavior, where the individual movement is defined as a one-dimensional, stochastic, and time/space discrete transition process. The simulation environment is capable of covering a broad range of behaviors, boarding strategies and operational constraints and allows the integration of infrastructural changes and future technologies. The paper provides a set of indicators for depicting the real-time status of the boarding progress as a fundamental basis for the prediction of the boarding time. In this context, the aircraft seats are used as a sensor network with the capability to detect the seat status: free or occupied. The seat status is the basis for the calculation of an aircraft-wide interference potential as the major indicator for the boarding time. In combination with an integrated airline/airport information management (e.g. sequence of boarding passengers), the boarding progress will be transformed from a black box to a transparent progress with the operator's real-time ability to react to significant deviations from the planned progress. Thus, the research results provide a fundamental contribution towards the derivation of the crucial aircraft departure time.